Mongolia's Strategic Partnership with India: The Third Neighbour Policy and Beyond - Chatterjee, Souvik; Baitha, Subhash Kumar (Social Inquiry: Journal of Social Science Research, 2022)
Following the collapse of its trusted ally, the USSR, Mongolia faced significant challenges in aligning itself within the new global order. As a result, Mongolia's external and internal strategic environment compelled the nomadic nation to establish and maintain friendly relations with major powers other than China and Russia. Mongolia has since attempted to diversify its diplomatic and strategic reach in regional and international forums that had previously been overshadowed by Mongolia's previous patron, the Soviet Union. Mongolia had adopted two distinct policies, namely the ‘Good Neighbor Policy’ and the ‘Third Neighbor Policy’, which outlined Mongolia's aspirations in the post-Cold War global order. This paper will attempt to understand the changes and continuities in Mongolian foreign policy as a result of Mongolia's 'Third Neighbour Policy,' as well as to investigate the possibility of mutual cooperation between India and Mongolia. The most important aspect of this research is identifying Mongolia's relevant security issues. This study will use empirical data to examine Mongolia's security dilemma, but the analysis will be qualitative. The study's findings show that, despite its small power status, Mongolia will play an important role in North Asian great power politics due to its geostrategic location and mineral resources. Given China's dominance and Western powers' counter-dominance initiatives, this assumption is becoming true. With this in mind, India started to transform it spiritual partnership with Mongolia into a comprehensive strategic one.